Self esteem dan nomophobia pada remaja: Peran mediasi loneliness - Juwita, Sarah; Iswinarti; Diah Karmiyati (Psychological Journal: Science and Practice, 2024)
Nomophobia is a form of discomfort, stress, or anxiety caused by the absence of a mobile phone or other virtualcommunication devices in individuals who frequently use smartphones. Nomophobia can be influenced by severalfactors, such as self esteem and loneliness. This study aims to examine the effect of self esteem on nomophobia,mediated by loneliness, in adolescents. A quantitative research method was employed in this study. The subjects were adolescents aged 13-18 years who are smartphone users, with a sample size of 513 respondents. The instruments used include the Nomophobia Questionnaire (NMP-Q), The Self-Liking/Self-Competence Scale (SLSC), and the University of California, Los Angeles Loneliness Scale Version 3 (UCLA Loneliness Scale Version 3). The analysis technique utilized was mediation analysis using the PROCESS macro by Hayes. The findings of this study indicate that loneliness acts as a mediator in the relationship between self esteem and nomophobia in adolescents, with significance (β = -0.207). It was found that the indirect effect or mediating role accounts for only 29% of the total effect, thus only partially mediating the relationship.